Development of System Continuance Models for Assessing among Local E-Government in Indonesia - Dody, Herdiana; Dwi, Yuniarto; Esa, Firmansyah; Mulya, Suryadi; A'ang, Subiyakto; Aedah, Abd Rahman (2018)
This study reports how to combine technology acceptance and use models based on expectations and confirmations in the information system success model to objectively assess the continuance of local e-government based on the organizational perspective and perspective of users in Indonesia. The developed model is arranged in 11 variables and 48 indicators. Pathways of influence between variables are presented by 16 links. However, this study does have some limitations. With regard to the level of use, there is no fully mandatory use of the system, and not all UTAUT2 variables and the possibility of a moderator are integrated with the model. Other studies used various assumptions, methods, and different understandings can present different propositions. In addition, limitations can help to further study, especially the validity of the proposed model. Future research can explore additional expansion variables and moderators, so that in the new model between variables can be made more explicit relationships.